Peningkatan Profesionalitas Guru Melalui Implementasi E-Pakem Model “Door To Door Visit Supervision” di UPTD SDN Pandiyangan 1 Kecamatan Robatal Kabupaten Sampang Tahun Pelajaran 2018/2019 - Lilis Suryani (Departement of Mathematics Education, 2023)
In the midst of the rampant training in the field of improving the quality of education including improving the learning process for elementary school teachers, there are still many teachers implementing conventional learning processes as a legacy of ancient teachers, on the other hand, several teachers who have done PAKEM are still limited to development. upgrading results. There is no learning innovation yet. This situation is caused by the fact that most school principals seem to be preoccupied with other administrative matters which take up a lot of time, so that supervision activities are neglected. From these problems, it is necessary to have activities that are very specific to writers in changing the teaching paradigm through Door to door Visit Supervision. Door to door visit supervision is intended to instill/promote supervision activities to school principals. to carry out coaching of the learning process for teachers to carry out PAKEM , because it will be visited by another Principal. So that the Principal before making visits to other schools to monitor the activities of the teacher's learning process in other schools, it is necessary to provide guidance to the teacher. From this activity it is hoped that there will be positive activities from the school principal to guide his teachers, before other school principals evaluate the teachers he supervises. The research method used is action research by determining the activity cycle through the steps of problem identification, planning, action , observation and reflection then followed by re-planning back to the next cycle. The research subjects were the principal and teachers in the supervision area. In addition to determining the iterative flow (cycle) in this study, data collection techniques, research instruments, and analysis techniques were formulated through two cycles. The research results from cycle I to cycle II from the data collected then analyzed turned out to show that there was a significant change in the process conventional learning has changed into PAKEM and those who have implemented PAKEM have become more effective, thus it can be concluded that door to door visit supervision is very appropriate to increase the effectiveness of PAKEM.